Life and scientific priorities of professor Myroslav Malovanyy - Vronska, Nataliya (Lviv Politechnic Publishing House, 2017)
This article describes the life and scientific priorities of professor Myroslav Malovanyy. It also provides details and results of a joint research with his students of a liquid media treatment from different types of pollution. The main research and its results are illustrated, as well as environmental technologies that were developed by using the archived results.
Keywords: research; natural sorbents; adsorption; environmental technology; integrated processes